Propuesta de un plan estratégico para la empresa “sin fronteras tienda de ropa” de la ciudad de Loja, periodo 2015-2019 - Granados Ulloa, Werner Eliut (2015)
Within the research that was conducted at the company without Borders clothing store, in order to improve the administrative aspect, organizational and customer the same and considering that doing business and selling does not mean just the fact of putting a product or service on display and sit and wait for someone else to buy, a situation they are facing most businesses and companies in the city of Loja, I've seen the need for a strategic plan for the company SHOP WITHOUT BORDERS OF CLOTHES. Research on "PROPOSAL FOR A STRATEGIC PLAN FOR THE COMPANY" CLOTHING STORE WITHOUT BORDERS "CITY OF LOJA, PERIOD 2015-2019" was developed in the city of Loja, with the general objective to develop a strategic plan In order to improve the economic and competitive development of the company, and that the strategic plan is an essential tool in any organization, it facilitates effective marketing of any product or service. This research consists of: Title, Summary, which corresponds to a summary of the relevant parts of the thesis; the introduction, in this the importance of the subject matter, whereby a comprehensive understanding of all the work done will be highlighted; The literature review, it consists of citations containing theoretical contexts on the strategic plan, such as: concepts and importance of the issues most commonly used in this work; Deductive, inductive and descriptive techniques such as direct observation, interview with the manager of the company and surveys both employees in a number of 6 and clients in a sample of materials and methods in which the methods are detailed 340 surveys, and procedures used in the investigation that led to collect the information necessary to determine facts and phenomena that occur in the environment of the company and identify the major internal and external problems affecting it were done, the same that have prevented solvency and normal development. The results, which are part detailing the internal analysis showed that the amount of 2.74 means that there are more strengths than weaknesses inside the company and external analysis showed the amount of 2.58 which means that the external environment there are more opportunities than threats for the company, which begins with a historical overview, situational analysis, macro and micro localization and business philosophy, then a SWOT analysis of the company takes place, in which the internal factors were determined as are the strengths and weaknesses and external factors are the opportunities and threats, then the matrix of high impact criteria and their respective percentages assessment is performed. In the discussion, in which a draft strategic plan was developed to improve the business of the company "CLOTHING STORE WITHOUT BORDERS" of the city of Loja, this consist of strategic objectives, which were: Strategic Objective No. 1 Train staff for efficient development of its activities and achieve customer loyalty to the company. Strategic Objective No. 2 Develop the administrative structure of the company "Sin Fronteras" that will improve the management and organization of the same. Strategic Objective No. 3 Make an advertising plan to attract more customers and increase sales of the company. Strategic Objective No. 4 Develop a plan for promotions in order to encourage customers to purchase the products of the company. In the conclusions, it emphasized the most important research with their respective recommendations, the most important situations obtained during the implementation of the analysis of the entire research work, so that the manager take the necessary corrective measures for described their entity